Xiomi / Muhammad Faiz Hazim Abdul Rahman - Abdul Rahman, Muhammad Faiz Hazim (2022)
In this assignment, the goal is to identify the problem with the product. My company of choice is Xiaomi Inc. which is one of well-known brands in the world. Out of their many products, I have chosen the Xiaomi 1S electric scooter for my analysis. Since, I already own one and try the electric scooter by myself, so it is easier for me to come up with specific and clear analysis. According to my SWOT analysis, I identified the strengths, weaknesses, opportunities, and threats of the Xiaomi 1S. The machine is not as effective in rain as other models by top brands, such as Ninebot Max, Aovo Pro, and others. As a result, I am able to propose an effective solution, which is an improved IP rating for Xiaomi 1S that will allow use in any weather conditions.